Comedores de porquerías : control y sanción de la alimentación indígena, desde la óptica española en el Nuevo Reino de Granada (siglos XVI y XVII) (2009)
ABSTRACT: Between the Sixteenth and Seventeenth centuries, Spanish people in Nuevo Reino de Granada built an image of indigenous groups as eaters of unacceptable products for human consumption. This was based upon food characteristics as well as practices and habits associated with food intake. The article explains the way in which these images were built and transformed and how these processes were directly linked with ideas related to the dichotomy of civilized or savage, but fundamentally to the concept of humanity and the characteristics assigned to this.